Pengaruh Lokasi, Persepsi Harga dan Citra Destinasi Terhadap Minat Berkunjung Kembali Pada Objek Wisata Telaga Sarangan Kabupaten Magetan - Ramadhani, Nuraulia Rizky; Sudaryanti, Dwiyani; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of location, price perception, and destination image on tourists’ intention to revisit the Telaga Sarangan Tourist Attraction in Magetan Regency. The research employs a quantitative approach using a survey method, where questionnaires were distributed to 377 respondents who had previously visited Telaga Sarangan. The collected data were then analyzed using SPSS software. The results indicate that all three variables have a positive and significant effect on tourists’ intention to revisit. These findings emphasize the importance of effective destination management, particularly through improving accessibility, setting prices in accordance with perceived value, and strengthening the destination image, in order to enhance visitor loyalty and encourage repeat visits. Keywords: Location, Price Perception, Destination Image, Revisit Intention